Dissemination of Resistant Escherichia coli Among Wild Birds, Rodents, Flies, and Calves on Dairy Farms - Hickman, Rachel A.; Agarwal, Viktoria; Sjöström, Karin; Emanuelson, Ulf; Fall, Nils; Sternberg-Lewerin, Susanna; Järhult, Josef D. (Frontiers in Microbiology, 2022)
Abstract: Antimicrobial resistance (AMR) in bacteria in the livestock is a growing problem, partly due to inappropriate use of antimicrobial drugs. Antimicrobial use (AMU) occurs in Swedish dairy farming but is restricted to the treatment of sick animals based on prescription by a veterinary practitioner. Despite these strict rules, calves shedding antimicrobial resistant Enterobacteriaceae have been recorded both in dairy farms and in slaughterhouses. Yet, not much is known how these bacteria disseminate into the local environment around dairy farms. In this study we collected samples from four animal sources (faecal samples from calves, birds and rodents, and whole flies) and two environmental sources (cow manure drains and manure pits). From the samples, Escherichia coli was isolated and antimicrobial susceptibility testing performed. A subset of isolates was whole genome sequenced to evaluate relatedness between sources and genomic determinants such as antimicrobial resistance genes (ARGs) and the presence of plasmids were assessed. We detected both ARGs, mobile genetic elements and low rates of AMR. In particular, we observed four potential instances of bacterial clonal sharing in two different animal sources. This demonstrates resistant E. coli dissemination potential within the dairy farm, between calves and scavenger animals (rodents and flies). AMR dissemination and the zoonotic AMR risk is generally low in countries with low and restricted AMU. However, we show that interspecies dissemination does occur, and in countries that have little to no AMU restrictions this risk could be underestimated.